305 ASSESSMENT OF REGULATORY T CELLS IN PHENOTYPIC TYPE 2 DIABETES PATIENTS. (1st January 2006) - Goel, A.; Brooks-Worrell, B.; Palmer, J. P.
Abstract : Type 1.5 diabetes or LADA comprises approximately 10% of Caucasian adult phenotypic type 2 diabetes patients. Autoantibodies and T cells reacting to islet proteins suggest an autoimmune pathogenesis, whereas classic type 2 patients are negative for autoantibodies and T cell responses to islet proteins. We hypothesize that regulatory cells are present in classic type 2 patients and are either decreased in numbers or function in type 1.5 patients. In this study, we asked whether regulatory cell (CD4+/CD38+ and CD4+/CD25+) numbers were similar in classic type 2 and type 1.5 patients. T cells were characterized by cellular immunoblotting and autoantibody responses (ICA/IAA/GAD/IA-2) to islet proteins were measured. Of 19 pheotypic type 2 diabetes patients, 6 were negative for both autoantibody (Ab-) and cellular immunoblotting responses (T cell-) to islet proteins, 8 patients were Ab-T cell+, and 5 patients were Ab+T cell+. The percentage of regulatory T cells was assessed by flowcytometry and beta cell function was measured by fasting and glucagon-stimulated C-peptide in the 3 subject groups. We observed no significant differences in the fasting C-peptide among the 3 groups. However, glucagon-stimulated C-peptide was significantly lower ( p < .05) in both T cell+ groups. We observed that CD4+/CD38+ and CD4+/CD25+ cells were significantly (p < .05) lower in Ab+T cell+ patients compared to both Ab-T cell+ and Ab-Tcell- patients. As expected the Ab+T cell+ group had lower beta cell function and decreased regulatory T cells compared to the Ab-T cell- and Ab-T cell+ groups. In contrast the Ab-T cell+ group, who demonstrate autoimmunity with positive T cell responses and lower beta cell function, had similar numbers of regulatory T cells as in Ab-T- group. A functional abnormality of regulatory T cells in such patients might be part of the explanation, which is currently under investigation. The defect in regulatory populations may allow for the progression of autoimmune response to islet proteins and subsequent decrease in beta cell function.